Persicaria hydropiper (L.) Delarbre: A review on traditional uses, bioactive chemical constituents and pharmacological and toxicological activities. (6th April 2020) - Ayaz, Muhammad; Ahmad, Irshad; Sadiq, Abdul; Ullah, Farhat; Ovais, Muhammad; Khalil, Ali Talha; Devkota, Hari Prasad
Abstract: Ethnopharmacological relevance: Various plant parts of Persicaria hydropiper (L.) Delarbre (Syn.: Polygonum hydropiper L., Family: Polygonaceae) are used in traditional medicine systems as astringent, sedative, antiseptic and also for the treatment of respiratory disorders, edema and snake bites. It is also used as a spice in many Asian countries. Aim of the review: The main aim of this review is to critically analyze the reported traditional uses, bioactive chemical constituents and pharmacological activities of P. hydropiper . Materials and methods: Scientific database including PubMed, Scopus, SciFinder and secondary resources including books and proceedings were searched using relevant terminologies related to P. hydropiper and available scientific information was critically analyzed. Results: Analysis of the scientific literature regarding the traditional uses revealed that P. hydropiper is used as a medicine and as spice in food preparations in various parts of the world. Various compounds including flavonoids, phenylpropanoid derivatives, and sesquiterpenoids among others were reported as active compounds. The extracts and compounds from P. hydropiper showed diverse biological activities including anti-inflammatory, antioxidant, cytotoxic, antimicrobial activities, etc. Conclusion: Although various research reports showed diverse biological activities for extracts and compounds obtained from P. hydropiper, very few studies were performed using animal models. Many of these studies also lacked proper experimental setting such as use of positive and negative controls and selection of dose as in most of these studies very high doses of extracts were administered. Further, as P. hydropiper is widely used in the treatment of snake bites and insect bites, such effects of extracts and/or compounds are not well explored. Future studies on P. hydropiper should be focused to establish the links between the traditional uses, active compounds and reported pharmacological activities. Graphical abstract: Image 1